Alkali-free and chlorine-free liquid accelerator for shotcrete and preparation method thereof
Patent Information
- Application Number
- CN202610930652.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-26
AI Technical Summary
[0003]目前市场上应用的主要是液体无碱速凝剂,普遍存在以下问题:(1)由于铝离子在水溶液中存在水解,低温环境下水解更快,硫酸铝的析晶分层,导致直接成品液体无碱速凝剂的稳定性差,进而影响无碱速凝剂的应用;(2)为了凝结时间和早期强度达到标椎,引入大量碱金属盐从而导致碱含量超标
1、本发明以生产便捷投入少及产品可有效应对水泥多样性为出发点,首先合成制备出具有超促凝早强且低含水物促凝早强母料膏体,该膏体少量(占胶材的2%-3%)可使水泥在1-2min初凝,3-4min终凝,1d强度≥5MPa。最后,根据不同水泥特性再选取合适的硫酸盐组合物进行复配得到性能优异的液体速凝剂。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to an alkali-free and chlorine-free liquid quick-setting agent for shotcrete and its preparation method. Background Technology
[0002] Shotcrete technology is widely used in engineering projects such as tunnels, rock walls, and mine reinforcement. Alkali-free accelerators, as essential admixtures in current shotcrete technology, directly determine the construction quality of shotcrete. As my country's requirements for shotcrete quality and construction environment continue to increase, the performance requirements for accelerators are also becoming increasingly stringent. Engineering projects in Northwest China, Sichuan, and Tibet provinces, due to harsh terrain, geology, and climate conditions, often involve a large proportion of tunnels and bridges, placing high demands on the reinforcement and support conditions inside tunnels. This necessitates high requirements for the setting time and early strength performance of alkali-free accelerators used in tunnel shotcrete reinforcement. While meeting the requirements of GB / T35159-2017 "Alkali-free Accelerators for Shotcrete," major engineering projects in tunnels also require mortar 24-hour strength ≥10MPa as specified in Q / CR807-2020 "Liquid Alkali-free Accelerators for Shotcrete in Tunnels," while the chloride ion content of the liquid alkali-free accelerator must be ≤0.05%, and the alkali content ≤1%.
[0003] Currently, the main type of liquid alkali-free quick-setting agent used in the market has the following problems: (1) Due to the hydrolysis of aluminum ions in aqueous solution, the hydrolysis is faster at low temperature. The crystallization and stratification of aluminum sulfate leads to poor stability of the finished liquid alkali-free quick-setting agent, which in turn affects the application of alkali-free quick-setting agent; (2) In order to achieve the standard setting time and early strength, a large amount of alkali metal salts are introduced, resulting in excessive alkali content. (3) The concentration is low and the water content is 45% to 60%, which undoubtedly increases the transportation cost of quick-setting agent products. (4) The existing alkali-free quick-setting agent formula usually fixes the ratio of aluminate and sulfoaluminate. This fixed ratio structure makes it unable to cope with the diversity of cement types and greatly limits its adaptability in different cement systems. Powder alkali-free quick-setting agents generally have the following problems: (1) When compounding to prepare liquid quick-setting agents, the proportion of core materials is 60-100%, which is costly. (2) Similarly, the product structure is fixed and cannot cope with the diversity of cement types. The above-mentioned defects result in a limited product coverage, making it difficult to expand the product's application scope and seriously affecting the development and promotion of quick-setting agents in the construction industry.
[0004] CN109851272A discloses a method for preparing an alkali-free powdered quick-setting agent, which requires drying and grinding to obtain the core product. Therefore, the production equipment and processes using this method are complex and costly, the energy consumption during production is extremely high, and the drying cycle is too long, significantly reducing production efficiency.
[0005] CN112142359A discloses a dry and wet sprayable powdered alkali-free quick-setting agent and its preparation and application method. The aluminum sulfate used in this method must be pretreated to remove most of the crystal water so that the water content is less than 4% before it can be mixed and ground. This process has high energy consumption. In addition, the prices of all the raw materials in this invention fluctuate greatly, making it difficult to control the preparation cost. Furthermore, mixing multiple powders will result in poor uniformity of the finished product, which is not conducive to large-scale production and use.
[0006] CN117534362A discloses a high-performance alkali-free quick-setting powder and its preparation method. The method mainly involves dissolving a stabilizer, aluminum sulfate, inorganic salt, and organic complexing agent uniformly at 60℃-70℃ to obtain a saturated precursor solution. The precursor solution is then reacted with inorganic nano-CSH microcrystals in a recirculating container of a rotary evaporator at high temperature (105℃-120°C). After the reaction, the mixture is cooled and ground to obtain the high-performance alkali-free quick-setting powder. This preparation method directly uses aluminum sulfate as a raw material, which lacks cost advantage. Furthermore, the high-temperature reaction and evaporation processes followed by grinding make the production process complex and require significant investment for industrial production, resulting in high production costs.
[0007] CN115521087A discloses a powdered alkali-free quick-setting agent and its preparation method. The agent uses industrial concentrated sulfuric acid, fluorosilicic acid (a byproduct of phosphate chemical industry), aluminum hydroxide, transparent powder, magnesium triphosphate, stabilizer, and water as raw materials. These materials react and solidify at room temperature, followed by simple crushing, drying, and grinding. While this preparation method is easily scalable, the use of a large amount of fluorosilicic acid, a byproduct of phosphate chemical industry, as a raw material, while significantly increasing setting time and possessing a strong ability to complex aluminum ions, makes it difficult for the quick-setting agent to meet the requirements of China National Railway Group's standard Q / CR807-2020 "Liquid Alkali-Free Quick-Setting Agent for Tunnel Shotcrete". Furthermore, this preparation method also requires simple crushing, drying, and grinding processes, resulting in high production investment and complex production technology. In addition, the long solidification time using transparent powder as a forming agent leads to a relatively long overall production cycle, and the hydrophobic nature of the transparent powder results in poor stability when the powdered quick-setting agent is mixed with water to form a liquid quick-setting agent.
[0008] CN120349111A discloses an alkali-free accelerator compounded with aluminate materials. Its main preparation method involves using aluminate matrix materials, sulfoaluminate matrix materials, regulators, aluminum sulfate, and water, through multi-stage stirring. The stirring speed reaches 1000-1500 r / min, and the entire process takes approximately 5-6 hours. While this preparation method optimizes the setting performance and strength development of the accelerator, improves its compatibility with cement and construction efficiency, and solves the problems of poor compatibility, long setting time, and slow strength development of traditional accelerators, thus meeting the requirements for rapid construction and high strength, the overall compounding process places high demands on production equipment and technology, resulting in significant production investment. Furthermore, the entire compounding process is time-consuming and energy-intensive. Summary of the Invention
[0009] To address the aforementioned technical problems, this invention provides an alkali-free and chlorine-free liquid quick-setting agent for shotcrete and its preparation method.
[0010] To achieve the above objectives, the technical solution of the present invention is as follows: A non-alkali and chloride-free liquid quick-setting agent for shotcrete, comprising tap water, a quick-setting and early-strength masterbatch paste, and sulfate; the mass percentages of each component are: tap water 38-48 parts, quick-setting and early-strength masterbatch paste 22-36 parts, and sulfate 25-32 parts, wherein the preparation steps of the quick-setting and early-strength masterbatch paste include: A. First, add 8-12 parts of tap water to the reactor. While heating, add 70-85 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 55-60℃, add 4-6 parts of active aluminum powder, 7-10 parts of mixed alkanolamine, and 2.5-4.5 parts of mixed alcohol in sequence. Stir at a stirring speed of 500-700 r / min for 20-30 min, then add 1.5-3 parts of organic acid agent, 4-7 parts of nano calcium carbonate, 0.5-0.8 parts of organic polymer, 0.5-0.7 parts of suspension stabilizer, and the remainder is water. C. Stir at a speed of 900-1500 r / min until uniform to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 15-20%.
[0011] Further, the preparation of the lithium aluminum sulfate polysiloxane colloid in step A is as follows: First, add 100-140g of distilled water to a four-necked flask. Under the conditions of stirring speed below 500r / min and temperature below 40℃, add 280g-320g of aluminum sulfate pentahydrate. After dissolving, add 13g-17g of sodium silicate and 23g-27g of sodium aluminate sequentially under a high shear stirring speed of 1300-1500r / min. After the addition is completed, maintain high shear stirring for 20-40min. During the stirring process, keep the temperature of the mixture below 35℃. Then, at a stirring speed of 500-800r / min, raise the temperature to 50-60℃ and add 50g-70g of lithium sulfate. Continue stirring at a constant temperature for 1.5h-2.5h, then allow it to cool naturally. Subsequently, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysiloxane sol.
[0012] Furthermore, the sulfate is of industrial grade and is composed of aluminum sulfate pentahydrate or aluminum sulfate octahydrate and one or a mixture of two of magnesium sulfate heptahydrate, ferric sulfate heptahydrate, and lithium sulfate.
[0013] Further, the mixed alcoholamine is a mixture of one or more of diethanolamine, triethanolamine, or isopropanolamine, with a mass percentage of 50-100%; the mixed alcohol is a mixture of one or more of ethylene glycol, glycerol, or methanol, with a mass percentage of 50-100%; and the organic acid is a mixture of one or more of oxalic acid, formic acid, lactic acid, tartaric acid, citric acid, and acetic acid.
[0014] Furthermore, the particle size of the nano-calcium carbonate is 1-100 nm.
[0015] Furthermore, the particle size of the nano-calcium carbonate is 10-50 nm.
[0016] Furthermore, the organic polymer is a mixture of water-soluble potassium polyacrylate, water-based sulfonated polystyrene, polyacrylamide, and polyvinyl alcohol in a mass ratio of 1:4:2:3; the suspension stabilizer is a mixture of modified hydrated magnesium silicate and modified calcium bentonite in a mass ratio of 4:1.
[0017] A method for preparing an alkali-free and chlorine-free liquid quick-setting agent for shotcrete includes the following steps: Step 1: Weigh out tap water, coagulating and early-strength masterbatch paste, and sulfate at room temperature; Step 2: Add the weighed materials into the reactor in sequence and stir to mix. The stirring speed of the reactor is 450 r / min. Stir for 40-60 minutes to obtain the liquid quick-setting agent.
[0018] Preferably, the prepared liquid accelerator is used in shotcrete at a dosage of 6%-9%.
[0019] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention focuses on convenient production with low input costs and the ability of the product to effectively address the diversity of cements. First, it synthesizes and prepares a masterbatch paste with ultra-fast setting and early strength and low water content. A small amount of this paste (2%-3% of the binder) can enable cement to initially set in 1-2 minutes, achieve final setting in 3-4 minutes, and reach a 1-day strength ≥ 5 MPa. Finally, suitable sulfate compositions are selected and compounded according to the different characteristics of cements to obtain a high-performance liquid accelerator.
[0020] 2. This invention introduces a large number of accelerators and early-strength components during the synthesis of a low-moisture, fast-setting, early-strength accelerator masterbatch paste, along with small-molecule carboxylic acids, organic polymers, and suspension stabilizers, forming a triple-stabilizing system that effectively prevents aluminum ion crystallization and stratification. The introduced nano-calcium carbonate forms a monomolecular protective film on the metal ion surface through electrostatic adsorption, improving the compatibility of the accelerator with cement. Simultaneously, due to the size effect and the formation of reactive substances (calcium formate, calcium lactate, etc.), it enhances the material's early strength, durability, and erosion resistance, improves pore structure, and reduces production costs.
[0021] 3. This invention simplifies the production process of alkali-free quick-setting agents, reduces production input, and lowers production costs. It solves the problems of current alkali-free quick-setting powders requiring drying and grinding processes, and the fact that commercially available powder quick-setting agents often have a 70%-100% main material ratio, hindering large-scale conversion and widespread application. It simplifies the production process of alkali-free and chlorine-free quick-setting agents, reducing production input and lowering production costs. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that these descriptions are merely exemplary and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concepts of the invention.
[0023] Example 1 This example provides a method for preparing a convenient, alkali-free, and chlorine-free liquid quick-setting agent for shotcrete at room temperature. The steps are as follows: At room temperature, add 48 parts by weight of drinking tap water, 30 parts by weight of sulfate, and 22 parts by weight of accelerator and early-strength masterbatch paste to a reactor and stir for 45 minutes at a stirring speed of 450 r / min until the mixture is dissolved and homogeneous to obtain the concrete quick-setting agent.
[0024] The preparation steps of the accelerated coagulation and early strength masterbatch paste include: A. First, add 8 parts of tap water to the reactor. While heating, add 70 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 55℃, add 4 parts of active aluminum powder, 7 parts of mixed alkanolamine, and 2.5 parts of mixed alcohol in sequence. Stir at a stirring speed of 500r / min for 20min, and then add 1.5 parts of organic acid agent, 4 parts of nano calcium carbonate, 0.5 parts of organic polymer, 0.5 parts of suspension stabilizer, and the remainder is water. C. Stir at 900 r / min until homogeneous to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 17%.
[0025] The preparation of the polyaluminum sulfate colloid in step A is as follows: First, add 100g of distilled water to a four-necked flask. Then, add 280g of aluminum sulfate pentahydrate under the conditions of stirring speed of 200r / min and temperature of 10℃. After dissolving, add 13g of sodium silicate and 23g of sodium aluminate in sequence under a high shear stirring speed of 1300r / min. After the addition is completed, maintain high shear stirring for 20min. During the stirring process, keep the temperature of the mixture below 35℃. Then, add 50g of lithium sulfate at a stirring speed of 500r / min and temperature of 50℃. Continue stirring at a constant temperature for 1.5h, then let it cool naturally. After that, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white polyaluminum sulfate sol.
[0026] The sulfate is of industrial grade and is composed of 24 parts aluminum sulfate pentahydrate and 6 parts magnesium sulfate heptahydrate.
[0027] The mixed alcoholamine is obtained by uniformly mixing 80% diethanolamine and 20% triethanolamine by mass.
[0028] The mixed alcohol is 100% ethylene glycol by mass.
[0029] The organic acid is a mixture of formic acid, lactic acid, tartaric acid, and citric acid in a ratio of 1:2:1:1.
[0030] Example 2 This example provides a method for preparing a convenient, alkali-free, and chlorine-free liquid quick-setting agent for shotcrete at room temperature. The steps are as follows: At room temperature, add 48 parts by weight of drinking tap water, 30 parts by weight of sulfate, and 24 parts by weight of accelerator and early-strength masterbatch paste to a reactor and stir for 50 minutes at a stirring speed of 450 r / min to dissolve and mix evenly to obtain the concrete quick-setting agent.
[0031] The preparation steps of the accelerated coagulation and early strength masterbatch paste include: A. First, add 9 parts of tap water to the reactor. While heating, add 71 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 56℃, add 4 parts of active aluminum powder, 7 parts of mixed alkanolamine, and 3 parts of mixed alcohol in sequence. Stir at a stirring speed of 520r / min for 22min, and then add 1.5 parts of organic acid agent, 4 parts of nano calcium carbonate, 0.6 parts of organic polymer, 0.5 parts of suspension stabilizer, and the remainder is water. C. Stir at 950 r / min until homogeneous to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 16.5%.
[0032] The preparation of the lithium aluminum sulfate polysiloxane colloid in step A is as follows: First, add 110g of distilled water to a four-necked flask. Then, add 290g of aluminum sulfate pentahydrate under the conditions of stirring speed of 360r / min and temperature of 19℃. After dissolving, add 13g of sodium silicate and 24g of sodium aluminate in sequence under a high shear stirring speed of 1300r / min. After the addition is completed, maintain high shear stirring for 20min. During the stirring process, keep the temperature of the mixture below 35℃. Then, raise the temperature to 52℃ at a stirring speed of 550r / min and add 56g of lithium sulfate. Continue stirring at a constant temperature for 1.5h. Allow it to cool naturally and then let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysiloxane sol.
[0033] The sulfate is of industrial grade and is composed of 24 parts of aluminum sulfate pentahydrate and 6 parts of ferrous sulfate heptahydrate. The mixed alcoholamine is obtained by uniformly mixing 60% diethanolamine, 20% triethanolamine, and 20% isopropanolamine by mass percentage.
[0034] The mixed alcohol is obtained by uniformly mixing 60% ethylene glycol, 20% glycerol, and 20% methanol by mass.
[0035] The organic acid is a mixture of oxalic acid, formic acid, lactic acid, and citric acid in a ratio of 1:1:2:1.
[0036] Example 3 This example provides a method for preparing a convenient, alkali-free, and chlorine-free liquid quick-setting agent for shotcrete at room temperature. The steps are as follows: At room temperature, add 47 parts by weight of drinking tap water, 28 parts by weight of sulfate, and 25 parts by weight of accelerator and early-strength masterbatch paste to a reactor and stir for 40 minutes at a stirring speed of 450 r / min to dissolve and mix evenly to obtain the concrete quick-setting agent.
[0037] The preparation steps of the accelerated coagulation and early strength masterbatch paste include: A. First, add 9 parts of tap water to the reactor. While heating, add 75 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 55℃, add 5 parts of active aluminum powder, 8 parts of mixed alkanolamine, and 3 parts of mixed alcohol in sequence. Stir at a stirring speed of 650r / min for 25min, and then add 2.5 parts of organic acid agent, 5 parts of nano calcium carbonate, 0.7 parts of organic polymer, 0.5 parts of suspension stabilizer, and the remainder is water. C. Stir at 1000 r / min until homogeneous to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 18%.
[0038] The preparation of the lithium aluminum sulfate polysiloxane colloid in step A is as follows: First, add 120g of distilled water to a four-necked flask. Then, add 300g of aluminum sulfate pentahydrate under the conditions of stirring speed of 450r / min and temperature of 30℃. After dissolution, add 15g of sodium silicate and 25g of sodium aluminate in sequence under high shear stirring speed of 1400r / min. After the addition is completed, maintain high shear stirring for 40min. During the stirring process, keep the temperature of the mixture below 35℃. Then, at a stirring speed of 600r / min, raise the temperature to 55℃ and add 60g of lithium sulfate. Continue stirring at a constant temperature for 2h, then let it cool naturally. After that, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysiloxane sol.
[0039] The sulfate is of industrial grade and is composed of 21 parts aluminum sulfate pentahydrate, 4 parts magnesium sulfate heptahydrate, and 3 parts lithium sulfate.
[0040] The mixed alcoholamine is obtained by uniformly mixing 80% diethanolamine and 20% triethanolamine by mass.
[0041] The mixed alcohol is obtained by uniformly mixing 50% ethylene glycol and 50% methanol by mass.
[0042] The organic acid is a mixture of formic acid, lactic acid, and citric acid in a ratio of 1:1:1.
[0043] Example 4 This example provides a method for preparing a convenient, alkali-free, and chlorine-free liquid quick-setting agent for shotcrete at room temperature. The steps are as follows: At room temperature, add 42 parts by weight of drinking tap water, 30 parts by weight of sulfate, and 28 parts by weight of accelerator and early-strength masterbatch paste to a reactor and stir for 58 minutes at a stirring speed of 450 r / min to dissolve and mix evenly to obtain the concrete quick-setting agent.
[0044] The preparation steps of the accelerated coagulation and early strength masterbatch paste include: A. First, add 11 parts of tap water to the reactor. While heating, add 80 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 58℃, add 6 parts of active aluminum powder, 9 parts of mixed alkanolamine, and 4.5 parts of mixed alcohol in sequence. Stir at a stirring speed of 600r / min for 30min, and then add 2 parts of organic acid agent, 5 parts of nano calcium carbonate, 0.7 parts of organic polymer, 0.5 parts of suspension stabilizer, and the remainder is water. C. Stir at 1400 r / min until homogeneous to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 19%.
[0045] The preparation of the lithium aluminum sulfate polysiloxane colloid in step A is as follows: First, add 100-140g of 120g of distilled water to a four-necked flask. Then, add 310g of aluminum sulfate pentahydrate under the conditions of stirring speed of 380r / min and temperature of 30℃. After dissolving, add 15g of sodium silicate and 25g of sodium aluminate in sequence under a high shear stirring speed of 1400r / min. After the addition is completed, maintain high shear stirring for 32min. During the stirring process, keep the temperature of the mixture below 35℃. Then, at a stirring speed of 600r / min, raise the temperature to 60℃ and add 70g of lithium sulfate. Continue stirring at a constant temperature for 2.5h, then let it cool naturally. After that, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysiloxane sol.
[0046] The sulfate is a mixture of 24 parts aluminum sulfate octadecahydrate, 4 parts magnesium sulfate heptahydrate, and 2 parts ferrous sulfate heptahydrate.
[0047] The mixed alcoholamine is obtained by uniformly mixing 50% triethanolamine and 50% isopropanolamine by mass percentage.
[0048] The mixed alcohol is obtained by uniformly mixing 30% ethylene glycol, 20% glycerol and 50% methanol by mass.
[0049] The organic acid is a mixture of lactic acid, tartaric acid, and citric acid in a ratio of 2:1:1.
[0050] Example 5 This example provides a method for preparing a convenient, alkali-free, and chlorine-free liquid quick-setting agent for shotcrete at room temperature. The steps are as follows: At room temperature, add 38 parts by weight of drinking tap water, 32 parts by weight of sulfate, and 30 parts by weight of accelerator and early-strength masterbatch paste to a reactor and stir for 60 minutes at a stirring speed of 450 r / min to dissolve and mix evenly to obtain the concrete quick-setting agent.
[0051] The preparation steps of the accelerated coagulation and early strength masterbatch paste include: A. First, add 10 parts of tap water to the reactor. While heating, add 78 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 55℃, add 4 parts of active aluminum powder, 7 parts of mixed alkanolamine, and 3 parts of mixed alcohol in sequence. Stir at a stirring speed of 600r / min for 22min, and then add 2 parts of organic acid agent, 5 parts of nano calcium carbonate, 0.7 parts of organic polymer, 0.6 parts of suspension stabilizer, and the remainder is water. C. Stir at 1200 r / min until homogeneous to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 16%.
[0052] The preparation of the lithium aluminum sulfate polysiloxane colloid in step A is as follows: First, add 130g of distilled water to a four-necked flask. Then, add 320g of aluminum sulfate pentahydrate under the conditions of stirring speed of 360r / min and temperature of 32℃. After dissolution, add 15g of sodium silicate and 26g of sodium aluminate in sequence under high shear stirring speed of 1300r / min. After the addition is completed, maintain high shear stirring for 35min. During the stirring process, keep the temperature of the mixture below 35℃. Then, raise the temperature to 55℃ at a stirring speed of 600r / min and add 65g of lithium sulfate. Continue stirring at constant temperature for 1.5h, then let it cool naturally. After that, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysiloxane sol.
[0053] The sulfate is a mixture of 25 parts aluminum sulfate octadecahydrate, 5 parts ferrous sulfate heptahydrate, and 2 parts lithium sulfate.
[0054] The mixed alcoholamine is obtained by uniformly mixing 90% diethanolamine and 10% triethanolamine by mass.
[0055] The mixed alcohol is obtained by uniformly mixing 90% ethylene glycol and 10% methanol by mass.
[0056] The organic acid is a mixture of formic acid, lactic acid, tartaric acid, and citric acid in a ratio of 1:2:1:1.
[0057] Example 6 This example provides a method for preparing a convenient, alkali-free, and chlorine-free liquid quick-setting agent for shotcrete at room temperature. The steps are as follows: at room temperature, add 40 parts by weight of drinking tap water, 26 parts by weight of sulfate, and 34 parts by weight of accelerator and early-strength masterbatch paste to a reactor and stir for 50 minutes at a stirring speed of 450 r / min to dissolve and mix evenly to obtain the concrete quick-setting agent.
[0058] The preparation steps of the accelerated coagulation and early strength masterbatch paste include: A. First, add 10 parts of tap water to the reactor. While heating, add 80 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 58℃, add 5 parts of active aluminum powder, 9 parts of mixed alkanolamine, and 4 parts of mixed alcohol in sequence. Stir at a stirring speed of 600r / min for 28min, and then add 2 parts of organic acid agent, 6 parts of nano calcium carbonate, 0.7 parts of organic polymer, 0.6 parts of suspension stabilizer, and the remainder is water. C. Stir at 1500 r / min until homogeneous to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 17%.
[0059] The preparation of the lithium aluminum sulfate polysiloxane colloid in step A is as follows: First, add 120g of distilled water to a four-necked flask. Then, add 320g of aluminum sulfate pentahydrate under the conditions of stirring speed of 450r / min and temperature of 30℃. After dissolution, add 15g of sodium silicate and 25g of sodium aluminate in sequence under a high shear stirring speed of 1450r / min. After the addition is completed, maintain high shear stirring for 35min. During the stirring process, keep the temperature of the mixture below 35℃. Then, at a stirring speed of 700r / min, raise the temperature to 55℃ and add 60g of lithium sulfate. Continue stirring at a constant temperature for 2h, then let it cool naturally. After that, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysiloxane sol.
[0060] The sulfate is a mixture of 20 parts aluminum sulfate octadecahydrate, 4 parts magnesium sulfate heptahydrate, and 2 parts lithium sulfate.
[0061] The mixed alcoholamine is obtained by uniformly mixing 80% diethanolamine, 10% triethanolamine, and 10% isopropanolamine by mass percentage.
[0062] The mixed alcohol is obtained by uniformly mixing 30% glycerol and 70% methanol by mass.
[0063] The organic acid is a mixture of lactic acid, tartaric acid, and citric acid in a ratio of 2:1:2.
[0064] Example 7 This example provides a method for preparing a convenient, alkali-free, and chlorine-free liquid quick-setting agent for shotcrete at room temperature. The steps are as follows: At room temperature, add 39 parts by weight of drinking tap water, 25 parts by weight of sulfate, and 36 parts by weight of accelerator and early-strength masterbatch paste to a reactor and stir for 60 minutes at a stirring speed of 450 r / min to dissolve and mix evenly to obtain the concrete quick-setting agent.
[0065] The preparation steps of the accelerated coagulation and early strength masterbatch paste include: A. First, add 12 parts of tap water to the reactor. While heating, add 85 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 60℃, add 6 parts of active aluminum powder, 10 parts of mixed alkanolamine, and 4.5 parts of mixed alcohol in sequence. Stir at a stirring speed of 700r / min for 30min, and then add 3 parts of organic acid agent, 7 parts of nano calcium carbonate, 0.8 parts of organic polymer, 0.7 parts of suspension stabilizer, and the remainder is water. C. Stir at 1500 r / min until homogeneous to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 19%.
[0066] The preparation of the lithium aluminum sulfate polysiloxane colloid in step A is as follows: First, add 140g of distilled water to a four-necked flask. Then, add 320g of aluminum sulfate pentahydrate under the conditions of stirring speed of 490r / min and temperature of 38℃. After dissolving, add 17g of sodium silicate and 27g of sodium aluminate in sequence under a high shear stirring speed of 1500r / min. After the addition is completed, maintain high shear stirring for 40min. During the stirring process, keep the temperature of the mixture below 35℃. Then, raise the temperature to 60℃ at a stirring speed of 800r / min and add 70g of lithium sulfate. Continue stirring at a constant temperature for 2.5h, then let it cool naturally. After that, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysiloxane sol.
[0067] The sulfate is a mixture of 20 parts aluminum sulfate pentahydrate and 5 parts lithium sulfate.
[0068] The super-mixed alcoholamine is obtained by uniformly mixing 80% diethanolamine, 5% triethanolamine, and 15% isopropanolamine by mass percentage.
[0069] The mixed alcohol is obtained by uniformly mixing 60% ethylene glycol, 10% glycerol, and 30% methanol by mass.
[0070] The organic acid is a mixture of lactic acid, citric acid, and acetic acid in a ratio of 2:1:1.
[0071] Comparative Example 1 The powdered alkali-free quick-setting agent, model HQ310, selected from Guizhou Shiboshi Technology Co., Ltd., was prepared by mixing masterbatch, aluminum sulfate, and water in a ratio of 40:20:40. At room temperature, 200g of water was first added to a 500ml four-necked flask, followed by 100g of aluminum sulfate octadeca. The mixture was stirred at a speed lower than 500r / min for about 30 minutes to dissolve the mixture. Then, 200g of masterbatch was added, and the mixture was stirred for 1.5 hours to prepare the liquid alkali-free quick-setting agent.
[0072] Comparative Example 2 The powder alkali-free quick-setting agent selected from Yunnan Kaiweite New Material Co., Ltd. was prepared by mixing masterbatch, aluminum sulfate, and water in a ratio of 40:20:40. At room temperature, 200g of water was first added to a 500ml four-necked flask, followed by 100g of aluminum sulfate octadeca. The mixture was stirred at a speed lower than 500r / min for about 30 minutes to dissolve the mixture. Then, 200g of masterbatch was added and stirred for 1.5 hours to prepare the liquid alkali-free quick-setting agent.
[0073] Comparative Example 3 The powdered alkali-free quick-setting agent, model SBT-N2, selected from Jiangsu Subote New Material Co., Ltd., was prepared by mixing masterbatch, aluminum sulfate, magnesium sulfate, and water in a ratio of 30:20:5:45. At room temperature, 150g of water was first added to a 500ml four-necked flask, followed by 100g of aluminum sulfate octadeca and 25g of magnesium sulfate. The mixture was stirred at a speed below 500r / min for about 40 minutes to dissolve the mixture. Then, 150g of masterbatch was added and stirred for 1.5 hours to prepare the liquid alkali-free quick-setting agent.
[0074] Test case The accelerators in Examples 1-7 and Comparative Examples 1-3 were subjected to stability testing in Experiment 1, and the test results are shown in Table 1. Experiment 2 used reference cement to test setting time, 1-day compressive strength, and 28-day compressive strength ratio, and the test results are shown in Table 2. Experiment 3 tested compatibility with different cements, including Pingliang Conch P.O42.5, Saima P.O42.5, Qilianshan P.O42.5, Hongshi P.O42.5, Hengya Zhongkang 42.5, and Ando P.O42.5, and the test results are shown in Table 3. The above performance testing methods followed GB / T35159-2017 "Liquid Alkali-Free Accelerators for Shotcrete," using standard sand. The accelerator dosage was 7 wt% of the cement.
[0075] Stability test in Experiment Example 1: Take 100ml of each of the liquid quick-setting agents from Examples 1-7 and Comparative Examples 1-3 and place them in a 100ml stoppered graduated cylinder to test their stability. The test results are shown in Table 1 below.
[0076] As can be seen from Table 1, the stability of Examples 4, 6 and 7 is qualified and the comparison ratio is excellent.
[0077] Experiment Example 2 Performance Test: The accelerators of the various embodiments and comparative examples of the present invention were mixed with cement (reference cement), and the dosage is shown in the table. The initial setting time, final setting time, rebound rate, 1-day compressive strength, and 28-day compressive strength ratio of the cement were recorded. The results are shown in Table 2 below.
[0078] As can be seen from the data in Table 2, the setting time and strength of the alkali-free and chlorine-free liquid quick-setting agents prepared in Examples 1-7 all meet the requirements of the national standard GB / T35159-2017 "Liquid Alkali-Free Quick-Setting Agent for Shotcrete" and have low rebound rate, good engineering performance, and better performance than commercially available comparative samples.
[0079] Experiment 3: Cement adaptability test Based on the results of Test Example 1 and Test Example 2, Example 6, which has the best overall performance, and Comparative Example 3 were used at the same dosage of 7% to test their adaptability to cement from various manufacturers. The results are shown in Table 3.
[0080] As can be seen from the data in Table 3, Example 6 showed better adaptability to both setting time and strength compared to Comparative Example 3 and different cements, while Comparative Example 3 had a poor ability to cope with the diversity of cements.
[0081] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features, without departing from the spirit and scope of the present invention. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such substitutions and modifications falling within the scope of the present invention are included in the appended claims. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the appended claims, or equivalent forms of such scope and boundaries.
Claims
1. An alkali-free and chloride-free liquid quick-setting agent for shotcrete, characterized in that, The liquid quick-setting agent is composed of tap water, a quick-setting and early-strength masterbatch paste, and sulfate; the mass fractions of each component are: tap water 38-48 parts, quick-setting and early-strength masterbatch paste 22-36 parts, and sulfate 25-32 parts. The preparation steps of the quick-setting and early-strength masterbatch paste include: A. First, add 8-12 parts of tap water to the reactor. While heating, add 70-85 parts of lithium aluminum sulfate polysilicate colloid while stirring. B. After heating to 55-60℃, add 4-6 parts of active aluminum powder, 7-10 parts of mixed alkanolamine, and 2.5-4.5 parts of mixed alcohol in sequence. Stir at a stirring speed of 500-700 r / min for 20-30 min, then add 1.5-3 parts of organic acid agent, 4-7 parts of nano calcium carbonate, 0.5-0.8 parts of organic polymer, 0.5-0.7 parts of suspension stabilizer, and the remainder is water. C. Stir at a speed of 900-1500 r / min until uniform to obtain the accelerated coagulation and early strength masterbatch paste, wherein the moisture content of the accelerated coagulation and early strength masterbatch paste is 15-20%.
2. The alkali-free and chloride-free liquid quick-setting agent for shotcrete according to claim 1, characterized in that, The preparation of the lithium aluminum sulfate polysilicate colloid in step A is as follows: First, add 100-140g of distilled water to a four-necked flask. Under conditions of stirring speed below 500r / min and temperature below 40℃, add 280g-320g of aluminum sulfate pentahydrate. After dissolving, add 13g-17g of sodium silicate and 23g-27g of sodium aluminate sequentially at a high shear stirring speed of 1300-1500r / min. After the addition is completed, maintain high shear stirring for 20-40min. During the stirring process, keep the temperature of the mixture below 35℃. Then, at a stirring speed of 500-800r / min, raise the temperature to 50-60℃ and add 50g-70g of lithium sulfate. Continue stirring at a constant temperature for 1.5h-2.5h, then allow it to cool naturally. Subsequently, let it stand and mature in a sealed container for 24 hours to obtain a white or grayish-white lithium aluminum sulfate polysilicate sol.
3. The alkali-free and chloride-free liquid quick-setting agent for shotcrete according to claim 1, characterized in that, The sulfate is of industrial grade and is composed of one or a mixture of two of the following: aluminum sulfate pentahydrate or aluminum sulfate octahydrate, magnesium sulfate heptahydrate, ferric sulfate heptahydrate, and lithium sulfate.
4. The alkali-free and chloride-free liquid quick-setting agent for shotcrete according to claim 1, characterized in that, The mixed alcohol amine is a mixture of several of the following by mass percentage: 50-100% diethanolamine, 0-50% triethanolamine, or 0-50% isopropanolamine; the mixed alcohol is a mixture of several of the following by mass percentage: 50-100% ethylene glycol, 0-50% glycerol, or 0-50% methanol; the organic acid is one or a mixture of several of the following: oxalic acid, formic acid, lactic acid, tartaric acid, citric acid, and acetic acid.
5. The alkali-free and chloride-free liquid quick-setting agent for shotcrete according to claim 1, characterized in that, The particle size of the nano-calcium carbonate is 1-100 nm.
6. The alkali-free and chloride-free liquid quick-setting agent for shotcrete according to claim 5, characterized in that, The particle size of the nano-calcium carbonate is 10-50 nm.
7. The alkali-free and chloride-free liquid quick-setting agent for shotcrete according to claim 1, characterized in that, The organic polymer is a mixture of water-soluble potassium polyacrylate, water-based sulfonated polystyrene, polyacrylamide, and polyvinyl alcohol in a mass ratio of 1:4:2:3; the suspension stabilizer is a mixture of modified hydrated magnesium silicate and modified calcium bentonite in a mass ratio of 4:
1.
8. A method for preparing an alkali-free and chloride-free liquid quick-setting agent for shotcrete according to any one of claims 1-7, characterized in that, Includes the following steps: Step 1: Weigh out tap water, coagulating and early-strength masterbatch paste, and sulfate at room temperature; Step 2: Add the weighed materials into the reactor in sequence and stir to mix. The stirring speed of the reactor is 450 r / min. Stir for 40-60 minutes to obtain the liquid quick-setting agent.
9. The method for preparing an alkali-free and chloride-free liquid quick-setting agent for shotcrete according to claim 8, characterized in that, The prepared liquid accelerator is used in shotcrete at a dosage of 6%-9%.
Citation Information
Patent Citations
Alkali-free powdery setting accelerator and preparation method thereof
CN109851272A
Dry and wet shotcrete dual-purpose powdery alkali-free accelerator, preparation method and use method thereof
CN112142359A
High-performance powder alkali-free accelerator and preparation method thereof
CN117534362A
Alkali-free aluminate material compound accelerator
CN120349111A
Liquid accelerator for calcium-containing aluminosilicate cementing material and preparation method for liquid accelerator
CN102617066A